A novel low‐power gate driver architecture for large 8 K 120 Hz liquid crystal display employing IGZO technology. Issue 5 (4th May 2018) - Iwase, Yasuaki; Tagawa, Akira; Takeuchi, Yohei; Watanabe, Takuya; Horiuchi, Satoshi; Asai, Yoshihiro; Yamamoto, Kaoru; Daitoh, Tohru; Matsuo, Takuya
Abstract: A novel low‐power gate driver architecture was developed for large 8 K 120 Hz liquid crystal display panel. For this application, not only high‐speed driving but also low power consumption is required. We employed a high mobility In‐Ga‐Zn‐O, dual VGL level driving method, and gate driver circuit driven by DC supply. The simulation results show that our proposals meet 8 K 120 Hz driving requirements. Also, we have fabricated a prototype panel and confirmed both high‐speed driving and low power consumption. Abstract : A novel low‐power gate driver architecture is developed for large scale 8 K 120 Hz liquid crystal display panel. For this application, high‐speed driving and low power consumption are required. We employed high mobility In‐Ga‐Zn‐O, dual VGL level driving method, and gate driver circuit driven by DC supply. We confirmed by simulation and a prototype panel.